S-adenosylmethionine and proliferation: new pathways, new targets. (19th September 2008) - Martínez-López, Nuria; Varela-Rey, Marta; Ariz, Usue; Embade, Nieves; Vazquez-Chantada, Mercedes; Fernandez-Ramos, David; Gomez-Santos, Laura; Lu, Shelly C.; Mato, Jose M.; Martinez-Chantar, Maria L.
Abstract : SAMe ( S -adenosylmethionine) is the main methyl donor group in the cell. MAT (methionine adenosyltransferase) is the unique enzyme responsible for the synthesis of SAMe from methionine and ATP, and SAMe is the common point between the three principal metabolic pathways: polyamines, transmethylation and transsulfuration that converge into the methionine cycle. SAMe is now also considered a key regulator of metabolism, proliferation, differentiation, apoptosis and cell death. Recent results show a new signalling pathway implicated in the proliferation of the hepatocyte, where AMPK (AMP-activated protein kinase) and HuR, modulated by SAMe, take place in HGF (hepatocyte growth factor)-mediated cell growth. Abnormalities in methionine metabolism occur in several animal models of alcoholic liver injury, and it is also altered in patients with liver disease. Both high and low levels of SAMe predispose to liver injury. In this regard, knockout mouse models have been developed for the enzymes responsible for SAMe synthesis and catabolism, MAT1A and GNMT (glycine N -methyltransferase) respectively. These knockout mice develop steatosis and HCC (hepatocellular carcinoma), and both models closely replicate the pathologies of human disease, which makes them extremely useful to elucidate the mechanism underlying liver disease. These new findings open a wide range of possibilities to discover novel targets for clinical applications.